2012
DOI: 10.1103/physrevd.85.104032
|View full text |Cite
|
Sign up to set email alerts
|

Black hole motion in Euclidean space as a diffusion process

Abstract: A diffusion equation for a black hole is derived from the BunsterCarlip equations. Its solution has the standard form of a Gaussian distribution. The second moment of the distribution determines the quantum of black hole area. The entropy of diffusion process is the same, apart from the logarithmic corrections, as the BekensteinHawking entropy.Bunster (Teitelboim) and Carlip showed [1] that the wave function of a black hole with the Arnowitt-Deser-Misner (ADM) mass M and area A evolves according to the Schrödi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recently, Ropotenko [20] showed that, by analogy with conventional Landau quantization, quantization of black hole is nothing but the Landau quantization. [21] This method is based on the standard commutation rules of quantum mechanics and makes use of the fundamental properties of the Euclidean Rindler space. As is wellknown, in transforming from Schwarzschild to Euclidean Rindler coordinates the Schwarzschild time transforms to a periodic angle w. This allows one to introduce the Hawking temperature T H .…”
Section: Area and Entropy Quantization For Non-extremal Gb Ds Black H...mentioning
confidence: 99%
“…Recently, Ropotenko [20] showed that, by analogy with conventional Landau quantization, quantization of black hole is nothing but the Landau quantization. [21] This method is based on the standard commutation rules of quantum mechanics and makes use of the fundamental properties of the Euclidean Rindler space. As is wellknown, in transforming from Schwarzschild to Euclidean Rindler coordinates the Schwarzschild time transforms to a periodic angle w. This allows one to introduce the Hawking temperature T H .…”
Section: Area and Entropy Quantization For Non-extremal Gb Ds Black H...mentioning
confidence: 99%
“…They provide the theory of diffusion problems in the Schwarzschild and Kruskal-Szekeres manifolds to represent the Black Holes. From the Bunster-Carlip equation, Ropotenko has derived a diffusion equation of black hole on Kerr-Newman space-time, and its solution has a Gaussian distribution form [31]. He also found the entropy of the diffusion process as well as the Bekenstein-Hawking entropy [32].…”
Section: Introductionmentioning
confidence: 99%
“…In [1], I derived a diffusion equation for a Schwarzschild black hole from the Bunster-Carlip equations and showed that the black hole evolution in Euclidean sector exhibits a diffusion process. Namely I showed that the Bunster-Carlip equationsh i ∂ψ ∂t + Mψ = 0,…”
mentioning
confidence: 99%
“…So, as in the case of a Schwarzschild black hole, one can introduce the corresponding temporal Θ and spatial τ coordinates for a Kerr-Newman black hole. I define the Hamiltonian of a Kerr-Newman black hole as that of a particle moving in the potential U = ΩJ + 1 2 ΦQ,…”
mentioning
confidence: 99%